2019
DOI: 10.1039/c9nj03167g
|View full text |Cite
|
Sign up to set email alerts
|

Step by step designing of sensitive luminescent nanothermometers based on Cr3+,Nd3+ co-doped La3−xLuxAl5−yGayO12 nanocrystals

Abstract: In this work we present step by step designing of sensitive luminescent thermometers utilizing Cr3+,Nd3+ co-doped La3−xLuxAl5−yGayO12 garnets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The high values of the S at temperatures above 400°C result from the low signal intensity. Nevertheless, the obtained S is comparable with the previously described results for other Cr 3+ based luminescent thermometers [18][19][20].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The high values of the S at temperatures above 400°C result from the low signal intensity. Nevertheless, the obtained S is comparable with the previously described results for other Cr 3+ based luminescent thermometers [18][19][20].…”
supporting
confidence: 90%
“…The energy at which this inter-section occurs, called activation energy, describes how efficient luminescence of transition metal ion will be quenched at elevated temperatures. In the case of Cr 3+ ions, which are one of the most extensively investigated, the 2 E excited state parabola intersects with the 4 T 2 one [11,12,[17][18][19][20]. Therefore at higher temperatures the non-radiative depopulation leads to the quenching of Cr 3+ emission intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, a number of works are performed aiming the optimization of the host material composition to alter the thermometric performance of the solely Cr 3+ -based LT [6,31,32,37]. Up till now, several approaches for lowering the crystal field strength, involving modification of the host material stoichiometry and the concentration of Cr 3+ dopant ions were described in detail [27,28,38]. It was shown that by gradual substitution of small ions such as Al 3+ by larger ions like Ga 3+ in octahedral sites of the host crystal matrix, the metal-oxygen bond distance gradually increased and should result in a decrease of the crystal field strength acting on incorporated Cr 3+ ions occupying these sites (Dq ∝…”
Section: Introductionmentioning
confidence: 99%
“…There are two general methodologies used in the Nd 3+ ‐based temperature sensors, corresponding to the stark splitting and thermal coupling between two energy states (excited or ground states) [32–35] . In recent years, to further enhance the temperature sensitivity and precision of relevant sensing devices, many co‐doping attempts with other Ln 3+ (Eu 3+ and Yb 3+ ) and transition (Cr 3+ , Mn 3+ , Ti 4+ , V 3+ , and Co 2+ ) luminescent ions were also conducted [36–39] . However, relative sensitivity ( S r ) of the current Nd 3+ ‐based sensing performance is still unsatisfactory and has a certain gap with semiconductor quantum dots and other Ln 3+ ‐based materials [23] .…”
Section: Introductionmentioning
confidence: 99%